Neonatally Induced Mild Diabetes in Rats and Its Effect on Maternal, Placental, and Fetal Parameters - Sinzato, Yuri Karen [UNESP]; Volpato, Gustavo Tadeu [UNESP]; Iessi, Isabela Lovizutto [UNESP]; Bueno, Aline [UNESP]; Calderon, Iracema de Mattos Paranhos [UNESP]; Rudge, Marilza Vieira Cunha [UNESP]; Damasceno, Débora Cristina [UNESP] (Hindawi Publishing Corporation, 2012)
The aim of this study was to assess placental changes and reproductive outcomes in neonatally induced mild diabetic dams and fetal development in their offspring. At birth, female rats were assigned either to control or diabetic group (100 mg of streptozotocin/Kg, subcutaneously). At adulthood, the female rats were mated. During pregnancy, the blood glucose levels and glucose and insulin tolerance tests were performed. At term, maternal reproductive outcomes, fetal and placental weight, and placental morphology were analyzed. Diabetic rats had smaller number of living fetuses, implantations and corpora lutea, and increased rate of embryonic loss. Placenta showed morphometric alterations in decidua area. Our results showed that mild diabetes was sufficient to trigger alterations in maternal organism leading to impaired decidua development contributing to failure in embryonic implantation and early embryonic losses. Regardless placental decidua alteration, the labyrinth, which is responsible for the maternal-fetal exchanges, showed no morphometric changes contributing to an appropriate fetal development, which was able to maintain normal fetal weight at term in mild diabetic rats. Thus, this experimental model of diabetes induction at the day of birth was more effective to reproduce the reproductive alterations of diabetic women.